A liquefied gas (freon r-134a) in an improved technology of extracting plant materials - Михайлов, Валерій Михайлович; Тімошенко, Юрій Петрович; Чуйко, Людмила Олексіївна; Михайлова, Світлана Володимирівна; Шевченко, Андрій Олександрович (Eastern-European Journal of Enterprise Technologies, 2015)
The study is aimed at improvement of the plant material extraction technology via the use of such extractant as ozone-friendly, azeotropic liquefied natural gas (Freon R-134a) and exploitation of adequate equipment for its implementation, which ensures higher process efficiency, resource conservation, and maintains the output quality. We set the following tasks: (1) to improve the plant material extraction technology via the use of ozone-friendly, azeotropic liquefied natural gas (Freon R-134a), (2) to design an extraction plant that would implement the technology, and (3) to use a resource saving technology for processing recycled plant materials in the study of the quality characteristics of the extracts. The object of the research is an improved technology of plant material extraction based on the use of liquefied gases (Freon types) and implemented due to an extraction plant. The subjects of the research include an extraction plant, grapes seed flour, red grapes peel, and the extracts derived from them. We have used a liquefied gas (Freon R-134a) to improve the technology of plant material extraction. The technology is based on maintaining a continuous liquefied-gas extraction of natural substances and removal of the solvent by means of a two-stage process of regeneration and condensation. This reduces the time of extraction, provides a better extraction of solvents from raw materials and finished products, increases the volume of a set of raw materials loaded in an extraction plant, and stabilizes the quality of manufactured products. The designed extraction plant promotes implementation of the appropriate technology of extracting plant materials by means of a liquefied gas (Freon R-134a). The construction comprises two consistently connected systems that include evaporators, condensers, storage tanks, refrigeration units, a receiver, and a vacuum pump. The plant allows continuous extraction of natural substances by means of liquefied gases. It can be used at industrial enterprises for the manufacture of food ingredients, cosmetics, and pharmaceuticals with physicochemical properties that are typical of initial raw materials of plant origin. The proposed technologies and equipment for extraction by means of liquefied gases provide the process efficiency, resource conservation, and stability of the quality characteristics of the manufactured products.